Opening up Jewish Education to Inspection - Keiner, Judy (Education Policy Analysis Archives, 1996)
Although Jewish schools in England are generally deemed successful, internal communal surveys have highlighted concerns about their teaching of Jewish studies and modern Hebrew. The UK government in 1993 established detailed national criteria for four-yearly published inspections of all schools. This imposed the need to develop criteria for the evaluation of these specifically Jewish subjects, and both schools and foundation bodies have begun to respond through training and development activities. Analysis of the first published reports, shows evidence of mismatch between Jewish schools' aims for Jewish Studies and their practice. Common findings on modern Hebrew teaching indicate concerns about planning, methodology and assessment. The response of Jewish communal bodies is explored, showing an increasing focus and some rivalry towards servicing the inspection and development needs of Jewish schools. Jewish communal press reporting and parental response to inspection is considered.